Antibiotic Utilization in Deceased Organ Donors. (20th May 2021) - Anesi, Judith A; Lautenbach, Ebbing; Han, Jennifer; Lee, Dong Heun; Clauss, Heather; Climaco, Antonette; Hasz, Richard; Bilker, Warren B; Molnar, Esther; Alimenti, Darcy; West, Sharon; Tolomeo, Pam; et al.
Abstract: Antibiotic use in deceased organ donors has not been previously described. In a retrospective cohort of 440 donors, we found 427 (97%) received at least one antibiotic course, 312 (71%) received broad-spectrum antibiotics, and 61 (14%) received potentially redundant antibiotics during their terminal hospitalization, suggesting a need for stewardship.